Nurse Knowledge About High Quality Cardiopulmonary Resuscitation (CPR) - Elyana Fadiah; Rismia Agustina; Oski Illiandri (Universitas Muhammadiyah Ponorogo, 2019)
High quality CPR is administering CPR with the standarts already specified by the American Heart Association (AHA) 2015 which consists of 5 main components. Based on the data obtained, as many as 3 people nurses said forgot about the depth of CPR and 1 the same nurse said forgot about the frequency of CPR. Nursing knowledge of high quality CPR is essential, in order to improve the effectiveness of action implementation. This study aims to determine of nurse’s knowledge about high quality CPR at IGD RSUD Ulin Banjarmasin. This research is a descriptive with cross-sectional method and sample of 34 people taken with total sampling technique. Instrument used in the form of questionnaires knowledge about the procedure of giving CPR and high quality CPR. Nursing knowledge level about high quality of CPR is less 1 (2,9%), enough 6 (17,6%) and good 27 (79,4%). The nurse's knowledge of high quality CPR is good, but it needs to be refreshed on CPR in order to improve the service for the better.